Impacts of CACNB4 overexpression on dendritic spine density in both sexes and relevance to schizophrenia - Emily M. Parker; Nathan L. Kindja; Rebecca A. DeGiosio; Ryan B. Salisbury; Josh M. Krivinko; Claire E. J. Cheetham; Matthew L. MacDonald; Weijia Fan; Bin Cheng; Robert A. Sweet (Translational Psychiatry)
Abstract The voltage-gated calcium channel (VGCC) subunit complex is comprised of the α1 subunit, the ion-permeable channel, and three auxiliary subunits: β, α2δ, and γ. β is the most extensively studied auxiliary subunit and is necessary for forward trafficking of the α1 subunit to the plasma membrane. VGCCs mediate voltage-dependent movement of calcium ions into neuronal cytoplasm, including at dendrites, where intracellular calcium spikes initiate signaling cascades that shape the structural plasticity of dendritic spines. Genetic studies strongly implicate calcium signaling dysfunction in the etiology of neurodevelopmental disorders including schizophrenia. Dendritic spine density is significantly decreased in schizophrenia in the primary auditory cortex where it is driven by the loss of small spines, and small spine loss associated with increased peptide levels of ALFDFLK found in the VGCC β subunit β4. Overexpressing the gene that encodes the voltage-gated calcium channel subunit β4, CACNB4, selectively reduced small spine density in vitro. In the current study we extended this observation in an intact mammalian system within a relevant neurodevelopmental context. We overexpressed CACNB4 in early development, assessed spine density and morphology in adult male and female mouse cortex, and characterized β1-4 protein levels and β4 protein-protein interactions. Overexpression reduced small spine density in females. This effect was not dependent on the estrous stage. Instead, it corresponded to sex differences in the murine β4 interactome. The VGCC subunit β1b was significantly enriched in the β4 interactome of male relative to female mice, and thus may have served to mitigate VGCC overexpression-mediated spine loss in male mice.